2021
DOI: 10.1590/2175-8239-jbn-2020-0080
|View full text |Cite
|
Sign up to set email alerts
|

Screening of family members of chronic kidney disease patients with Fabry disease mutations: a very important and underrated task

Abstract: Introduction: Fabry disease is a chronic, progressive, and multi-system hereditary condition, related to an Xq22 mutation in X chromosome, which results in deficiency of alpha-galactosidase enzyme, hence reduced capacity of globotriaosylceramide degradation. Objectives: to evaluate the prevalence of Fabry disease (FD) mutations, as well as its signs and symptoms, among relatives of chronic kidney disease (CKD) patients diagnosed with FD during a previously conducted study, named “Clinical and epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
0
0
1
Order By: Relevance
“…This number reflects the X-linked inheritance pattern of Fabry disease and suggests that the incidence of Fabry disease in women can be estimated at 1/20.000, compared to the traditional incidence of 1/40,000 in men18. Similarly, a screening study in patients with chronic kidney disease on hemodialysis therapy in Brazil showed an incidence of 66.1% in women, very similar to data from the present study 21 .…”
Section: Discussionsupporting
confidence: 90%
“…This number reflects the X-linked inheritance pattern of Fabry disease and suggests that the incidence of Fabry disease in women can be estimated at 1/20.000, compared to the traditional incidence of 1/40,000 in men18. Similarly, a screening study in patients with chronic kidney disease on hemodialysis therapy in Brazil showed an incidence of 66.1% in women, very similar to data from the present study 21 .…”
Section: Discussionsupporting
confidence: 90%
“…Esse número reflete o padrão de herança ligado ao X da doença de Fabry e sugere que a incidência da doença de Fabry em mulheres pode ser estimada em 1/20.000, comparada à incidência tradicional de 1/40.000 em homens 18 . De maneira semelhante, um estudo de rastreio em pacientes com doença renal crônica em terapia de hemodiálise no Brasil demonstrou incidência de 66,1% em mulheres, muito semelhante aos dados do presente estudo 21 .…”
Section: Discussionunclassified